Export Market Development and Institutional Support for Micro and Small Enterprise Internationalization - Jofret Umbu Soru Peku Djawang; Alya Elita Sjioen; Melvin Krisdiani Djame Rane; Yudith Febrianty Lerrick; Margarethy Rohanie Mbado; Yunialdi Hapynes Teffu (Department of Economics Education, Faculty of Economics, Universitas Negeri Makassar, 2026)
This study examines the factors influencing export market development among micro and small enterprises, with particular attention to the roles of internal readiness, export capacity, institutional support, and external barriers. Despite growing opportunities in international trade, many enterprises continue to face challenges related to market access, regulatory compliance, product competitiveness, and limited international business networks. A quantitative research design was employed using survey data collected from 100 micro and small enterprise actors. Data were analyzed using Partial Least Squares Structural Equation Modeling to evaluate measurement validity, structural relationships, and mediation effects. The findings reveal that internal readiness and export capacity significantly influence the effectiveness of government and institutional support. Institutional support also demonstrates a significant effect on reducing external barriers and facilitating export market development. Furthermore, government and institutional support serve as an important mediating mechanism through which internal capabilities influence firms’ ability to overcome external constraints. The study contributes to the international entrepreneurship and export development literature by demonstrating the strategic role of institutional support in transforming firm-level capabilities into export competitiveness. Drawing on the resource based view, institutional theory, and absorptive capacity theory, the findings suggest that strengthening enterprise capabilities should be accompanied by coordinated policy interventions, targeted export assistance programs, and stronger institutional ecosystems to enhance international market participation and long-term export performance.